TAFSIR AYAT HIJAB: ANALISIS METODE TAFSIR RAWAIUL BAYAN MUHAMMAD ALI ASH SHABUNI - Hariyono, Andy; Lutfiah, Ida (STIQ Al-Lathifiyyah Palembang, 2019)
This study discussed the method of tafsir Rawaiul Bayan by Muhammad Ali Ash Shabuni is related to hijab, especially in Surah Annur ayah 30-31. Ash Shabudi prioritised his overview that wearing of veil (cadar) is obligated. On the other hand, the referral literature used is dissagred that woman?s face is ashame. This literature study uses Rawaiul Bayan as fundamental literature.